Maqashid Syariah dan Urgensinya dalam Pembentukan Karakter Melalui Peran Guru PAI - Rudiansyah, Firman; Jaya, Hendri (An Naba, 2024)
This study emphasizes the importance of the maqashid sharia (Islamic principles) in shaping students' character through the key role of Islamic Religious Education (PAI) teachers. Using a qualitative-descriptive method based on library research, this study examines classical and contemporary literature on maqashid, character education, and Islamic Religious Education (PAI) pedagogical strategies. The analysis shows that the five main objectives of sharia—protecting religion, life, mind, lineage, and property—align with the core values of Islamic character education. Islamic Religious Education (PAI) teachers serve not only as transmitters of material but also as moral role models and facilitators of contextual moral development. The integration of maqashid into learning encourages the development of students who are faithful, moral, critical, and socially aware. This study recommends improving teachers' pedagogical competence and deepening their philosophical understanding of maqashid sharia to ensure character education remains relevant and effective in the modern era.